The Entwinement of Macroscale Welfare Politics and Microscale Masculine Performance An exploration of patriarchy through personal performances of masculinity in Denmark and Australia - Levin, Phoebe (Culture and History: Student Research Papers, 2017)
This paper draws a correlation between the adverse welfare systems of Denmark and Australia and their varying displays of masculinity in the form of personal gender performance. It utilises Puberty Blues and Twist and Shout, similar films regarding their genres, contexts and target audiences to exemplify the latter. It employs Judith Butler’s methodology, that gender expressions echo the social mores of the society in which they are conducted, to illuminate the inextricable link between macroscale constructions of masculinity, in the form of patriarchy and therein the differing economic-political systems of Denmark and Australia, and microscale performances. In doing this, it highlights how contingent upon sexuality gender expression was in the 1980’s, whilst also depicting the entwinement of the welfare states and their concomitant masculinities. It therefore argues that while the production of masculinity through individual and collective performance was simultaneously sustaining in the 1980’s in both nations, varying initial conceptions of masculinity influenced how they were solidified by superstructures and subsequently carried out.